Correlation of bronchial brushing cytology with bronchial biopsy in diagnosis of lung cancer - Piya, Eva; Sayami, Geeta; Srivastava, Brajendra (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Lung cancer is one of the leading cause of death in western countries and is the second most common malignancy in Nepal. Fiberoptic bronchoscopy has an excellent result in diagnosis of lung cancer when combined with brushing cytology & biopsy. This prospective study was conducted at Tribhuvan University Teaching Hospital over the period of one year with the aim to correlate brushing cytology with biopsy in diagnosis of bronchoscopically visible lung cancer. Method: A total of 62 cases were included in this study on whom bronchoscopy was performed in endoscopy unit. Bronchial brushing, biopsy specimens were collected & processed accordingly. Results: Out of 62 cases, 53 were found to be malignant and 9 were inflammatory lesions. Thus, cytohistological correlation was done in 53 malignant cases. There were 38 male and 15 were female with a mean age of 54 years. The male:female ratio was 2.5:1. The most common type of carcinoma was squamous cell carcinoma (64.2%), followed by adenocarcinoma (18.8%), small cell carcinoma(13.2%), large cell carcinoma (1.9%), carcinoid tumor (1.9%). Sensitivity of the bronchial brushing was 94.6% while that of biopsy was 91.3%. Conclusion: Bronchial brushing cytology has better detection rate than biopsy in this study. However combination of these modaliti es gives higher detecti on rate for bronchoscopically visible tumor. Therefore, bronchial brush cytology should be performed whenever possible in all suspected cases of lung cancer. DOI: http://dx.doi.org/10.3126/mjsbh.v10i2.6454 Medical Journal of Shree Birendra Hospital July-Dec 2011 10(2) 4-7